Customized Nasal Irrigation Strategies for Chronic Rhinosinusitis: A Comparative Trial of Additive-Based vs. Plain Saline Solution - Muhammad Amjad Obaid, Bilal Zahid, Navpreet Kaur, Ahsan Qureshi, Anees Ur Rehman, Ahmed Hassan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Chronic rhinosinusitis (CRS) remains a prevalent condition, often managed through nasalirrigation with saline solutions. This study aimed to evaluate the efficacy of additive-based nasal irrigation solutions